Direct estimates of prevalent HIV infection in adults in England and Wales for 1991 and 1993: an improved method. Issue 5 (October 1997) - Petruckevitch, A; Nicoll, A; Johnson, A M; Bennett, D
Abstract : OBJECTIVE: To estimate the number of prevalent HIV infections in England and Wales at the end of 1991 and 1993. METHOD: A direct method was used whereby population estimates derived from the National Survey of Sexual Attitudes and Lifestyle (NATSAL) and prevalence data from the Unlinked Anonymous HIV Prevalence Monitoring Programme (UAPMP) were combined to produce estimates of the number of adults infected and alive in the population. RESULTS: In the population of England and Wales the numbers of prevalent infections for defined transmission categories, at the end of 1993, were as follows: 12, 600 through sex between men, 2500 through injecting drug use, and 6900 through heterosexual intercourse. The overall estimate was 22, 800 HIV seropositive individuals. CONCLUSIONS: The direct method attempts to provide an estimate of the number of HIV infections using population based survey data. These estimates are consistent with other approaches using independent methods. Such methods are essential for inferring recent HIV incidence, projecting future AIDS cases, and for healthcare planning.